2013
DOI: 10.3171/2012.12.jns12908
|View full text |Cite
|
Sign up to set email alerts
|

Training to acquire psychomotor skills for endoscopic endonasal surgery using a personal webcam trainer

Abstract: Novices using this unique webcam trainer showed improvement in psychomotor skills for EES. The authors believe that training in terms of basic endoscopic skills is meaningful and that the webcam training system can play a role in daily off-the-job training for EES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Numerous studies evaluating the use of 3D technology in an ENT setting have suggested that it shortens the learning curve for novice surgeons, and others advocate its use in surgical training . In their landmark article, the Southern Surgeons Club group found that 90% of endoscopic surgical complications occurred in the first 30 patients of the learning curve, with the initial risk being tenfold of that after 50 operations .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies evaluating the use of 3D technology in an ENT setting have suggested that it shortens the learning curve for novice surgeons, and others advocate its use in surgical training . In their landmark article, the Southern Surgeons Club group found that 90% of endoscopic surgical complications occurred in the first 30 patients of the learning curve, with the initial risk being tenfold of that after 50 operations .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple training models of EES offer varying levels of realistic experiences to improve surgeon knowledge, surgical skills, confidence, and potentially patient outcomes. 8,10,18,19 Similarly, endovascular vascular injury models have been developed to provide more realistic training. Valentine et al proposed the use of a large animal model that would recreate high-flow, high-pressure injury and allow for objective assessment of the success in management with an evaluation of pre-and postinjury mean arterial pressure, mean resuscitation volume, mean blood loss, and survival time.…”
Section: Discussionmentioning
confidence: 99%
“…2,6 Acknowledging this, several groups are developing vascular injury models for appropriate training. [7][8][9][10][11] Despite their success, we suspect that current skull base courses may not adequately prepare surgeons to manage this complication and may foster interest in attempting extended approaches, which may inadvertently lead to increased incidence of vascular injury.…”
Section: Introductionmentioning
confidence: 99%
“…neurotrainer (Prodelphus, Germany), Phacon sinus system (Phacon, Leipzig, Germany), and Kezlex endoscopic models (Ono and Co., Tokyo, Japan), or provide only the basic training of hand-eye coordination. [17] The presented models provided good training of hand-eye coordination, instrument manipulation, dexterity, fine dissection, cutting, drilling, and simulation of laminectomies and removal of ligamentum flavum. These models were also used to teach the basic concepts of neuroendoscopy.…”
Section: Discussionmentioning
confidence: 99%